64.4k views
4 votes
Look at the example below which shows how the product property of radicals is used to simplify a radical. square root (-36)= square root (36) square root (-1) = 6i Use the product property of radicals to simplify the following radical. square root -81 =

User Rdougan
by
5.5k points

2 Answers

6 votes

Answer:

9i

Explanation:

hope this helps

User Bonnie
by
5.6k points
4 votes

Answer:

9i

Explanation:

Use the product property of radicals to simplify the following radical.


√(-81)

-81 can be break into 81 times -1

that is 81 and -1

as per the product property


√(-81) =√(81) * √(-1)

square root (-1) is 'i'

square root (81) is 9


√(-81) =√(81) * √(-1)


√(-81) =9* i


√(-81) =9i

User Rob Moll
by
5.2k points